Bank risk taking and competition: Evidence from regional banking markets - Thomas Kick; Esteban Prieto (Deutsche Bundesbank, 2013)
This study investigates the bank competition-stability nexus using a unique regulatory dataset provided by the Deutsche Bundesbank over the period 1994 to 2010. First, we use outright bank defaults as the most direct measure of bank risk available and contrast the results to weaker forms of bank distress. Second, we control for a wide array of different time-varying characteristics of banks which are likely to influence the competition-risk taking channel. Third, we include different measures of competition, contestability and market power, each corresponding to a different contextual level of a bank's competitive environment. Our results indicate that political implications derived from empirical banking market studies must recognize the theoretical properties of the indicators for market power and competition. Using the Lerner Index as a proxy for bank-specific market power, our results support the view that market power tends to reduce banks' default probability. In contrast, using the Boone Indicator (derived on the state level) and/or the regional branch share as a measure of competition, we find strong support that increased competition lowers the riskiness of banks.
Keywords: C35; G21; G32; L50; 330; bank risk; bank competition; instrumental variables models